2010
DOI: 10.4137/ehi.s4108
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial Activity of Some Medicinal Plants Used in Sudanese Folk-medicine

Abstract: Ten plants indigenous to Sudan and of common use in Sudanese folk-medicine, were examined in vitro for antimalarial activity against schizonts maturation of Plasmodium falciparum, the major human malaria parasite. All plant samples displayed various antiplasmodial activity. Three plant extracts caused 100% inhibition of the parasite growth at concentrations of plant material ≤ 500 ug/ml. The two most active extracts that produced 100% inhibition of the parasite growth at concentration of plant material ≤ 50 μg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 15 publications
(16 reference statements)
0
22
0
1
Order By: Relevance
“…Significant at P<0.05 level LC 50 lethal concentration that kills 50% of the exposed larvae, LC 90 lethal concentration that kills 90% of the exposed larvae, UCL upper confidence limit, LCL lower confidence limit, χ2 Chi-square, df degree of freedom quinquefasciatus. In vitro test for antimalarial activity against schizonts maturation of P. falciparum, the major human malaria parasite, the active extracts that produced 100% inhibition of the parasite growth at concentration of plant material ≤50 μg/ml were obtained from the whole plant of A. bracteolata (Ahmed et al 2010 Kamaraj et al (2009) have reported that the highest larval mortality was found in leaf petroleum ether, flower methanol extracts of Cryptocoryne auriculata, flower methanol extracts of Leucas aspera and R. nasutus, leaf and seed methanol extracts of Solanum torvum, and leaf hexane extract of Vitex negundo against the larvae of A. subpictus (LC 50 =44.21,44.69,53.16,41.07,35.32,28.90,and 44.40 ppm;LC 90 =187.31,188.29,233.18,142.66,151.60,121.05,and 192.11 ppm,respectively) (Chowdhury et al 2009). Bacillus thuringiensis subsp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant at P<0.05 level LC 50 lethal concentration that kills 50% of the exposed larvae, LC 90 lethal concentration that kills 90% of the exposed larvae, UCL upper confidence limit, LCL lower confidence limit, χ2 Chi-square, df degree of freedom quinquefasciatus. In vitro test for antimalarial activity against schizonts maturation of P. falciparum, the major human malaria parasite, the active extracts that produced 100% inhibition of the parasite growth at concentration of plant material ≤50 μg/ml were obtained from the whole plant of A. bracteolata (Ahmed et al 2010 Kamaraj et al (2009) have reported that the highest larval mortality was found in leaf petroleum ether, flower methanol extracts of Cryptocoryne auriculata, flower methanol extracts of Leucas aspera and R. nasutus, leaf and seed methanol extracts of Solanum torvum, and leaf hexane extract of Vitex negundo against the larvae of A. subpictus (LC 50 =44.21,44.69,53.16,41.07,35.32,28.90,and 44.40 ppm;LC 90 =187.31,188.29,233.18,142.66,151.60,121.05,and 192.11 ppm,respectively) (Chowdhury et al 2009). Bacillus thuringiensis subsp.…”
Section: Discussionmentioning
confidence: 99%
“…The whole plant extract of Aristolochia bracteolata was examined in vitro for antimalarial activity against schizonts maturation of P. falciparum (Ahmed et al 2010). Study focuses on the antibacterial and antifungal activity of the medicinal plant aqueous, methanol, and chloroform extracts of A. bracteolata tested against Escherichia coli, Bacillus subtilis, Staphylococcus aureus, Klebsiella pneumoniae, Pseudomonas fluorescens, Shigella flexneri, Proteus vulgaris, and Aspergillus niger, Aspergillus terreus, Penicillium notatum, and Rhizopus stolonifer (Kavitha and Nirmaladevi 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Sudanese medicinal plants have been reported to exert antimicrobial activity against viruses, bacteria, and protozoa. [19][20][21][22][23] As infections with worms or molluscs represent a common affliction in that area, medicinal plants have been considered for treatment of these infections. [24][25][26][27] Immunomodulatory properties of Sudanese medicinal plants have also been observed.…”
Section: Traditional Sudanese Medicinementioning
confidence: 99%
“…Frequentemente encontrada no Centro-Oeste brasileiro, em áreas de matas ciliares do domínio Cerrado, é uma das espécies de Aristolochia empregada na fitoterapia pela população matogrossense e sul mato-grossense (Lorenzi & Matos, 2008, Lorenzi & Souza, 2008. As ações fitomedicinais conhecidas são, na promoção da analgesia, como antidiurético, antiinflamatório, antibacteriano, antiparasitário e como agente antioxidante (Papuc et al 2010;Ahmed et al 2010, Aleixo et al 2014.…”
Section: Introductionunclassified